FEATURES OF RESTORING THE PERFORMANCE OF KARATE KILLERS IN THE CONDITIONS OF A BUSY COMPETITION SCHEDULE (American Journal of Technology and Applied Sciences, 2024)
This article analyzes the recovery process for karatekas in kumite, particularly during a busy competition schedule. It examines the physiological, neuromuscular, hydration, and cognitive components of fatigue that develop during multiple bouts over the course of one or more competition days. Based on an analysis of current scientific data, key principles and priorities for recovery are summarized, taking into account limited rest periods between bouts. The most effective recovery strategies applicable directly during competition are presented. It is demonstrated that effective recovery in kumite should be multi-component and phased, including active recovery, rehydration, carbohydrate supplementation, sleep management, and heat stress management.